Climate induced changes on fishing activities of artisanal fisher folks in the coastal area of Ogun State (2015)
The climate induced changes on the fishing activities of artisanal fisher folks was investigated in Ogun Waterside Local Government Area of Ogun State. Daze were obtained from one hundred and twelve fisher men using simple random sampling technique. Data analysis was done through the use of descriptive and inferential statistics (Chi-square, t-test at p=0.05 Findings show most respondents were male (90.2%). married 92 2% and mostly used family labour (80.3%). Most (69.6%) of the respondents used fishing net of various mesh sizes and The majority 72.3% of the fisher folk used unmotorized boats and traditionals. Factors influencing changes in fishing activities include reduction of volume of fish catch (79 5%), damage of nets and boats by ocean surges (50.4%), wind storm (59.8%), flooding of dwelling house and fa—-srz 84.8% and problem of fuel wood (81.3%).Coping strategies emearked upon by the fisher folks to combat the effect of climate charge were channelization of beels to Atlantic ocean (90.2%), construction of plant foot bridges (83.9%) and the use of hard wood to construct canoes (61.6%). More than half of the respondents (56.2%) had unfavourable perception of climate change on the extinction of fish species There were significant relationship between age (age x2=7 730). household size (x2=155.479) and volume of fish caught. There was a significant difference between the volume of fish caught ten years ago and now (t=22.427). Climate change has impacted negatively on the fishing activities of the artisanal fisher folks. It is recommended that metrological stations need to be resuscitated and well equipped in human resource and modem equipment to function effectively in climate information dissemination.